2011
DOI: 10.2147/trrm.s12212
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome of everolimus treatment in transplant patients

Abstract: Abstract:The authors review the use of everolimus in long-term studies both in renal and heart transplantation. The pharmacokinetic and pharmacodynamic differences between everolimus and its parent drug, sirolimus are discussed. The improved pharmacokinetic, in particular the improved bioavailability, the reduced half-time and the reduced binding to plasma protein makes everolimus the first choice among the proliferation signal inhibitors. Everolimus is given in almost all studies in association with cyclospor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 56 publications
(55 reference statements)
1
9
0
Order By: Relevance
“…5 Our data revealed that the mean EVR trough levels of the medium-dose and high-dose groups obtained 12 hours after third but right before the last EVR administration were above the therapeutic threshold of 3 ng/mL and, therefore, comparable to therapeutic treatments. 2,5 Although EVR has been systemically washed out since study day 8, the observed anti-proliferative effects even persist 5 days after the last EVR administration in the medium-dose and high-dose groups, whereas for IL-10 suppression this was just the case in the highdose group. These findings suggest that higher doses of EVR induce residual immunosuppressive effects even when the drug is completely metabolized.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…5 Our data revealed that the mean EVR trough levels of the medium-dose and high-dose groups obtained 12 hours after third but right before the last EVR administration were above the therapeutic threshold of 3 ng/mL and, therefore, comparable to therapeutic treatments. 2,5 Although EVR has been systemically washed out since study day 8, the observed anti-proliferative effects even persist 5 days after the last EVR administration in the medium-dose and high-dose groups, whereas for IL-10 suppression this was just the case in the highdose group. These findings suggest that higher doses of EVR induce residual immunosuppressive effects even when the drug is completely metabolized.…”
Section: Discussionsupporting
confidence: 49%
“…2,4 So far, EVR is the only clinically used mTOR inhibitor approved by the US Food and Drug Administration (FDA) for the oral administration and treatment of malignancies, including breast carcinoma, gastrointestinal tract-derived neuroendocrine tumors, renal cell carcinoma, and to prevent allograft rejection after heart, kidney, and liver transplantations. 1,2,5 Pharmacokinetic studies with transplant recipients obtaining EVR either with 0.75 mg/dose or 1.5 mg/dose twice a day combined with cyclosporin revealed maximal blood concentration of 11.1 ± 4.6 ”g/L and 20.3 ± 8.0 ”g/L, respectively, after 1 to 2 hours. 6,7 The elimination half-life amounts for 18-32 hours and steady-state is achieved between 4 and 7 days.…”
Section: Everolimus Effects On Psychoneuroimmune Levelmentioning
confidence: 99%
“…The decrease in everolimus dosage the day of introduction of voriconazole could not prevent the important increase in everolimus concentration and could have been accountable for the worsening of the patient's pulmonary symptoms. The estimated elimination half‐life of everolimus was twice higher the average reported value as the consequence of high voriconazole concentration and inhibitory effect on intestinal and hepatic CYP3A . As previously described with azole agents, this interaction is most likely a consequence of CYP3A4 inhibition .…”
Section: Case Descriptionmentioning
confidence: 53%
“…Everolimus is a 40-O-(2-hydroxyethyl) derivative,54 which was developed to improve the pharmacokinetic profile of sirolimus. The hydroxyethyl group provides a pharmacokinetic advantage, conferring faster absorption and a shorter half-life than sirolimus 55–57. Unlike sirolimus, no loading dose is required for everolimus, and the twice-daily dosing schedule allows better dose adjustments 57…”
Section: Role Of Immunosuppression In Liver Transplantationmentioning
confidence: 99%